Clinical effects of local use of probiotics as an adjunct to non-surgical periodontal therapy - Adamović Tijana; Trtić Nataša; Janković Ognjenka; Veselinović Valentina; Umićevic-Davidović Mirjana; Đukić Igor; Pavlić Verica (Serbian Medical Society - Dental Section, Belgrade, 2021)
Introduction Periodontal disease is a chronic inflammatory disease caused by pathologic microorganisms/periopathogens from oral biofilm. Standard periodontal therapy consists of scaling and root planing (SRP). Probiotics can be used as an adjunctive to standard periodontal therapy, since it is known that probiotics can modify pathogenic potential of biofilm by suppressing the colonization of periopathogens. The aim of this study was to assess the clinical effect of Bifidobacterium and Lactobacillus probiotic lozenges, probiotic mouthwash, as an adjuvant to SRP in the treatment of initial to moderate chronic periodontitis. Material and methods Thirty patients with initial to moderate chronic periodontitis were recruited and monitored clinically at baseline (before SRP) and 60 days following SRP. All patients were randomly assigned to experimental group: SRP + probiotic (n = 15) and control group: SRP only (n = 15). The probiotic mouthwash was used twice a day for 60 days. Clinical parameters: the probing pocket depth (PPD), clinical attachment level (CAL) and bleeding on probing (BOP) were measured at baseline and 60th day following SRP. Data were statistically analyzed using the one-way Anova test and SPSS 19 software (IMB Company, New York, U.S.). The Friedman and Mann Whitney tests were used as a post hoc test for intergroup analysis. Statistical significance was set at p < 0.05. Results After 60 days of treatment, the clinical parameters PPD, CAL and BOP were significantly lower in both groups compared to the baseline. In the experimental group, the clinical parameters PPD, CAL and BOP were significantly reduced after 60 days of treatment compared to the initial measurements (p < 0.05). In the control group, statistically significant decrease after 60 days of treatment was recorded only for BOP parameter, while there was no statistically significant decrease of PPD and CAL values (p > 0.05). Conclusion The results of the present study demonstrated clinical benefits of adjunctive use of probiotics to SRP in terms of pocket depth reduction in initial to moderate periodontal disease.